Employee Performance Analysis Based on Work Stress, Compensation, and Human Relations at PT Mazarzo Kreatif Indonesia - Melinda Putri Aprilia Simatupang; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The event and wedding organizer industry has a dynamic and high-pressure work environment; therefore, factors such as work stress, compensation, and human relations are essential elements in determining employee performance. This study aimed to analyze the influence of work stress, compensation, and human relations on employee performance at PT Mazarzo Kreatif Indonesia. This research was an associative study using a quantitative approach. The population in this study consisted of employees of PT Mazarzo Kreatif Indonesia. The sampling technique used was non-probability sampling with a saturated sampling method. Data analysis was conducted using multiple linear regression to examine the simultaneous and partial effects of the independent variables on employee performance. The results showed that work stress, compensation, and human relations simultaneously had a significant effect on employee performance. Partially, work stress had a significant negative effect on performance, indicating that the higher the level of work stress, the lower the employee performance. Compensation had a positive and significant effect on performance, suggesting that fair compensation increased work motivation and productivity, which led to improved performance. Meanwhile, human relations also had a positive and significant effect on performance, meaning that a harmonious work environment and good communication enhanced employee work effectiveness.